How long can you hold on? Physical self-efficacy predicts performance estimation accuracy independent of leisure-time physical activity - Meixner, Friedrich; Wölfle, Sophia; Hawat, Nizar (Frontiers in Psychology, 2025)
IntroductionAccurately estimating future performance is crucial for optimizing performance in sports and exercise. In our study, we aimed to explore the relationship between physical self-efficacy and the accuracy of performance estimation in various physical exercises.MethodsData were collected from N = 31 students (M = 23.5 years, n = 23 female, BMI 17–30, not engaged in any competitive sports). Measurements included questionnaires on physical activity and physical self-efficacy. Participants estimate their performance in five exercises, prior to performing them: (a) dumbbell hold, (b) plank, (c) vertical jump, (d) grip strength and (e) flamingo balance test.ResultsIndependently of leisure-time physical activity, participants underestimated their performance in these exercises. Physical self-efficacy was neither associated with levels of intense, leisure-time physical activity (r = 0.243, p > 0.05), nor with objective performance (all p > 0.05). However, physical self-efficacy was significantly associated with greater accuracy in performance estimation across all exercises (p < 0.01). These relationships were not mediated by leisure-time physical activity.ConclusionPhysical self-efficacy was positively associated with the congruency between estimation and objective performance, independent of leisure-time physical activity. These findings contribute to self-regulation research by emphasizing self-efficacy as a key factor in performance estimation accuracy, prioritizing cognitive mechanisms over behavioral engagement in self-assessment, and highlight its potential relevance in coaching and self-regulation.